Answer: the answer is c
Step-by-step explanation:
Answer:
The answer is
<h2>( 2 , 1)</h2>
Step-by-step explanation:
The midpoint M of two endpoints of a line segment can be found by using the formula
![M = ( \frac{x1 + x2}{2} , \: \frac{y1 + y2}{2} )](https://tex.z-dn.net/?f=M%20%3D%20%28%20%5Cfrac%7Bx1%20%2B%20x2%7D%7B2%7D%20%20%2C%20%5C%3A%20%20%5Cfrac%7By1%20%2B%20y2%7D%7B2%7D%20%29)
where
(x1 , y1) and (x2 , y2) are the points
From the question the points are
(-4,-8) and (8, 10)
The midpoint is
![M = ( \frac{ - 4 + 8}{2} , \: \frac{ - 8 + 10}{2} ) \\ = ( \frac{4}{2} , \frac{2}{2} )](https://tex.z-dn.net/?f=M%20%3D%20%28%20%5Cfrac%7B%20-%204%20%2B%208%7D%7B2%7D%20%20%2C%20%5C%3A%20%20%5Cfrac%7B%20-%208%20%2B%2010%7D%7B2%7D%20%29%20%5C%5C%20%20%3D%20%28%20%5Cfrac%7B4%7D%7B2%7D%20%2C%20%20%5Cfrac%7B2%7D%7B2%7D%20%29)
We have the final answer as
<h3>( 2 , 1)</h3>
Hope this helps you
Answer:
287.7 u gotta be kidding,
Step-by-step explanation:
42×6.85=287.7
Answer:
53
Step-by-step explanation:
At first,
- 7 = 9 + x
By subtracting 9 from both sides, we get
-7-9=9+x-9
-16=x
Now,
By substituting the value of x in -3x + 5 , we get
-3x + 5
-3×(-16)+5
48+5
53